A Chromosome-Scale Assembly of the Asian Honeybee Apis cerana Genome - Wang, Zi-Long; Zhu, Yong-Qiang; Yan, Qing; Yan, Wei-Yu; Zheng, Hua-Jun; Zeng, Zhi-Jiang (Frontiers in Genetics, 2020)
Apis cerana is one of the main honeybee species in artificial farming, which is widely distributed in Asian countries. The genome of A. cerana has been sequenced by several different research groups using second generation sequencing technologies. However, it is still necessary to obtain more complete and accurate genome sequences. Here we present a chromosome-scale assembly of the A. cerana genome using single-molecule real-time (SMRT) Pacific Biosciences sequencing and high-throughput chromatin conformation capture (Hi-C) genome scaffolding. The updated assembly is 215.67 Mb in size with a contig N50 of 4.49 Mb, representing an ∼212-fold improvement over the previous Illumina-based version. Hi-C scaffolding resulted in 16 pseudochromosomes occupying 97.85% of the assembled genome sequences. A total of 10,741 protein-coding genes were predicted and 9,627 genes were annotated. Besides, 314 new genes were identified compared to the previous version. The improved high-quality A. cerana reference genome will provide precise sequence information for biological research of A. cerana.